Electrospinning: Application and Prospects for Urologic Tissue Engineering - Zamani, Masoud; Shakhssalim, Nasser; Ramakrishna, Seeram; Naji, Mohammad (Frontiers in Bioengineering and Biotechnology, 2020)
Functional disorders and injuries of urinary bladder, urethra, and ureter may necessitate the application of urologic reconstructive surgeries to recover normal urine passage, prevent progressive damages of these organs and upstream structures, and improve the quality of life of patients. Reconstructive surgeries are generally very invasive procedures that utilize autologous tissues. In addition to imperfect functional outcomes, these procedures are associated with significant complications owing to long-term contact of urine with unspecific tissues, donor site morbidity, and lack of sufficient tissue for vast reconstructions. Thanks to the extensive advancements in tissue engineering strategies, reconstruction of the diseased urologic organs through tissue engineering have provided promising vistas during the last two decades. Several biomaterials and fabrication methods have been utilized for reconstruction of the urinary tract in animal models and human subjects; however, limited success has been reported, which inspires the application of new methods and biomaterials. Electrospinning is the primary method for the production of nanofibers from a broad array of natural and synthetic biomaterials. The biomimetic structure of electrospun scaffolds provides an ECM-like matrix that can modulate cells’ function. In addition, electrospinning is a versatile technique for the incorporation of drugs, biomolecules, and living cells into the constructed scaffolds. This method can also be integrated with other fabrication procedures to achieve hybrid smart constructs with improved performance. Herein, we reviewed the application and outcomes of electrospun scaffolds in tissue engineering of bladder, urethra, and ureter. First, we presented the current status of tissue engineering in each organ, then reviewed electrospun scaffolds from the simplest to the most intricate designs, and summarized the outcomes of preclinical (animal) studies in this area.